Company Size, Financial Distress And Audit Complexity Against Audit Report Lag - Arianti, Baiq Fitri (Universitas Gorontalo, 2021)
The purpose of this study is to measure and test thecompany size, financial distress, and audit complexity on audit report lag either partially or simultaneously. The type of research used is quantitative research with associative methods. The sample method in this study used a purposive sampling technique with a total sample of 7 miscellaneous industry sector companies and petroleum and natural gas obtained from the annual report for 5 years of observation as many as 35 annual reports 2015-2019. The data analysis technique used in this research is descriptive statistical analysis, classical assumption test, multiple regression test, and hypothesis testing with the help of the SPSS version 25 software program. The results of this study indicate that partially company size affects the audit report lag, financial distress variables. it does not affect the audit report lag, and audit complexity has an effect on the audit report lag. Meanwhile, the simultaneous test shows that all independent variables affect the audit report lag.